Comparison of spirometric functions in patients with asthma who underwent laparoscopic gastric bypass versus laparoscopic sleeve gastrectomy: A retrospective study (Annals of Medical Research, 2021)
Aim: Morbid obesity has become a global problem in our day, and different surgical methods are used in its solution. We aimed to compare the spirometric function results of asthmatic morbid obese who underwent laparoscopic sleeve gastrectomy (LSG) versus laparoscopic roux n y gastric bypass (LGB).Materials and Methods: We have retrospectively reviewed seventy two asthmatic patients who underwent LSG and LGB for morbid obesity between march 2016 and january 2020 in pulmonology department. Demographic findings, spirometrıc outcomes, and hospital stay were assessed. Statistically significant results were accepted as p 0.001.Results: The mean age of the participants in the study was 34.13±5.28 (mean age range 25-37), mean BMI 47.3 ± 3.4 kg / m2 (range 43-55). All of the operations were terminated laparoscopically Multivariate logistic regression analysis identified the independent prognostic factors for lung symptoms as age, gender and BMI. Age p:0.064, (OR(95%CI):2.036 [0.955, 4.341]), BMI,p:0.0791. (OR(95%CI): 895 [0.948, 3.789]), gender p:0.110(OR(95%CI):,0.978 [0.951, 1.005]) detected as shown.Conclusion: Although the laparoscopic gastric bypass procedure has a higher morbidity rate than laparoscopic sleeve gastrectomy, we have concluded that the healing effect in spirometric function tests and improvement in pulmonary outcomes are better.